Novel fermented beverage using selenized lactic acid bacteria - Martínez, Fernando Gabriel (2022)
Selenium (Se) is an essential micronutrient present as selenocysteine in seleno-enzymes, which are involved in aged-related diseases. Some lactic acid bacteria can reduce inorganic Se salts into seleno-amino acids. Se ingestion is usually below the recommended dietary intake (RDI). The ability of Se-enriched (selenized) Levilactobacillus brevis CRL2051 and Fructobacillus tropaeoli CRL2034 to resist different stress culture conditions was evaluated to further use these strains in a mixed starter culture for beverage fermentation. Selenization increased resistance to bile salts (10 %) of L. brevis CRL2051 and to oxidative stress (17 %, 8-h incubation) of F. tropaeoli compared to non-selenized cells, respectively. However, no differences in acid stress resistance by both selenized strains were found. A fermented milk-orange-mango juice was formulated using selenized cells of both strains, which could grow and biotransform inorganic Se into Se-amino acids (45.2 µg/L) after 14 h of incubation. Also, the strains survived a 52-day storage period and in vitro gastrointestinal tract conditions. After intestinal digestion, selenocysteine and selenomethionine were detected (25.8 and 2.4 µg/L, respectively) in the soluble beverage fraction. These results showed that intake of 250 ml of this fermented drink provides 64% of the Se RDI, of which 28% is composed of seleno-amino acids.